Retention Mechanism of Branched Macromolecules in Size Exclusion Chromatography - Netopilík, M.; Podzimek, Štěpán (My University, 2020)
The theory of Stockmayer in the modifications of Thurmond and Zimm has been used for the description of the size exclusion chromatography separation of randomly branched molecules with tetrafunctional branch points. It is assumed that free chain ends, created by the branching process, cause the molecules to be entrapped in the pores of the column packing with the time of their release given by the exponential law characteristic for the monomolecular reactions. Using this assumption, the anomalous elution behavior of such molecules can be modeled. With increasing elution volume, the average values of radius of gyration and, to a lesser degree, of molecular weight decrease and, after passing a minimum, again increase in the low-molecular weight region.
Retenční mechanismy větvených polymerů v gelové permeační chromatografii
Keywords: size exclusion chromatography; retention mechanisms; branched polymers; gelová permeační chromatografie; retenční mechanismus; větvené polymery